Mesa Redonda: «¿Un Impuso Efectivo a la Economía?: Alcances del último paquete de normas tributarias para promover la inversión en el Perú» - Hernández Patiño, Cecilia (2014)
In the last months, we have lived an environment of economic slowdown, which has led the Executive to legislate on various topics in order to boost the economy. Thus, this event will aim to generate debate about the latest package of tax regulations to promote investment in Peru with emphasis on the suspension of Rule XVI of the Tax Code and tax stability agreements.